2020
DOI: 10.1002/adom.201901326
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Broadband Cavity‐Free Lasers Based on All 2D Metamaterials

Abstract: all 2D materials, unlike gapless graphene, monolayer transition metal dichalcogenide (TMDC), such as MoS 2 , has attracted considerable attention in electronics, optoelectronics, spintronic applications due to their chiral optical properties, [7,8] relatively high carrier mobility, and tunable bandgap. [9][10][11][12][13][14][15][16] In particular, the unique mechanical flexibility makes TMDC and graphene materials as the most attractive candidates to satisfy the requirement of flexible optoelectronic devices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In additional, in recent reports, it has been observed that a rippled structure is an excellent matrix for photon trapping, as illustrated in Figure 4f. [ 16,26,46,58 ] As a result, the scattered photons get reabsorbed in the device, diminishing the scattering loss of photons, which in turn contributes to the photoresponsivity and gain.…”
Section: Resultsmentioning
confidence: 99%
“…In additional, in recent reports, it has been observed that a rippled structure is an excellent matrix for photon trapping, as illustrated in Figure 4f. [ 16,26,46,58 ] As a result, the scattered photons get reabsorbed in the device, diminishing the scattering loss of photons, which in turn contributes to the photoresponsivity and gain.…”
Section: Resultsmentioning
confidence: 99%
“…The detector can also be used for flammable, toxic, and harmful gases such as CH 4 , CO, and C 2 H 6 in the midinfrared region and SO 2 F 2 and SF 6 in the far-infrared [28]. It can also be used in thermal imaging [29], hyperspectral imaging [30], meteorology [31], free-space light [32], communication [33], remote sensing [34], and lasers [35] and for identifying biological compounds [36].…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties mainly arise as the electrodes used to inject charge carriers into the 2D semiconducting channel often consist of metal thin films, which break when the strain applied to the film is above 5% . To alleviate this issue, there have been previous works in which prestretched PDMS is able to maintain the integrity of the contact electrodes, while instigating compressive strain onto 2D materials, forming a rippled structure. ,,, Although this is a viable method to study the effects of uniaxial strain on BP, there are still limited studies on the effects of strain on the optoelectronic properties of BP, as these works were focused solely on the optical or electrical properties, respectively. , …”
Section: Introductionmentioning
confidence: 99%